2004
DOI: 10.1093/ndt/gfh130
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and illness intrusiveness in patients on chronic dialysis

Abstract: Sleep disorders are important determinants of illness intrusiveness and health-related quality of life in patients with ESRD. Sleep problems may be treated successfully; therefore, more attention should be paid to assessing these problems in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
3
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 18 publications
8
75
3
11
Order By: Relevance
“…In our study, we also found that these habits did not contribute to the insomnia severity score. A few studies have suggested that number and severity of comorbidity in hemodialysis patients can be attributed with the increase in the prevalence of sleep disorders [2,4,30]. In our study, we found that ischemic hearth disease was an independent determinant of the insomnia severity score.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In our study, we also found that these habits did not contribute to the insomnia severity score. A few studies have suggested that number and severity of comorbidity in hemodialysis patients can be attributed with the increase in the prevalence of sleep disorders [2,4,30]. In our study, we found that ischemic hearth disease was an independent determinant of the insomnia severity score.…”
Section: Discussionsupporting
confidence: 57%
“…Studies have been reported to range from 45% to 90% [4][5][6][7][8][9][10][11]. Insomnia occurs at an early stage chronic kidney disease (CKD), too [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…45 The original instrument was used in an epidemiologic survey 46 and the Hungarian version was used in our earlier studies involving different populations with CKD. [47][48][49] Comorbidity was assessed by the modified Charlson Comorbidity Index 50 completed by the main responsible transplant physician of the participant. Information about medication use was obtained from the questionnaires and the medical charts.…”
Section: Assessment Of Insomnia Restless Legs Syndrome and Comorbidmentioning
confidence: 99%
“…poor sleep quality is related to worse quality of life and increased morbidity and mortality in these patients (14)(15)(16). A wide variability of the incidence of certain sleep disorders in patients on dialysis, ranging from 30 -80%, indicates inadequately defined criteria for their diagnosis and previous lack of valid instruments for identifying specific disorders (15).…”
Section: Discussionmentioning
confidence: 99%